Delver - Reed, M. K. (Dark Horse Books, 2021)
"When the door to a living dungeon surfaces in the tiny hamlet of Oddgoat, village girl Temerity Aster has two choices: abandon the only home she's ever known to carpet baggers and sellswords, or carve out a place for herself and her family in the new and dangerous world of delving"--